Single visit endodontic in pulpitis irreversible is it effective? A case report - Indriyatmi, Rosida; Dwiandhany, Wahyuni S. (Hasanuddin University, 2022)
Objective: This case report aims to describe effectiveness of single visit endodontic in pulpitis irreversible.Methode: A 30 year-old female was referred to Dental Hospital of Hasanuddin University with chief complaint tooth cavities of mandibular molar and pain Â± 2 years ago, with the history of sudden pain and took paracetamol to relieve the pain. Patient did not go to dentist. Intraoral examination showed caries in Â 36, positive vitality, negative percussion and palpation. Radiograph showed normal periapical tissue. Endodontic treatment was performed in single visit endodontic with a single length preparation technique. Sequential irrigation was carried out using 5.25% NaOCl, 17% EDTA, and distilled water, and activated. Obturation performed with the single cone gutta percha technique with resin based sealer cement followed by direct composite restorationResult: Patient showed no complaints of pain and restoration was in good conditionConclusion: Single visit endodontic is an effective treatment for pulpitis irrversible